Anti-adhesion and anti-biofilm activity of slightly acidic electrolyzed water combined with sodium benzoate against Streptococcus mutans: A novel ecofriendly oral sanitizer to prevent cariogenesis. (May 2022) - Chen, Xiuqin; Tyagi, Akanksha; Vijayalakshmi, Selvakumar; Chelliah, Ramachandran; Shabbir, Umair; Oh, Deog-Hwan
Abstract: Streptococcus mutans ( S. mutans ) can promote the establishment of high acidic biofilms and therefore have contribution to the development of dental caries. Alleviating the acidic environment and/or disrupting the structure of S. mutans biofilm are effective approaches against dental caries, rather than killing the microorganisms. The anti -biofilm effect of slightly acidic electrolyzed water (SAEW) is entirely based on the hypochlorous acid and ROS generation. In this study, sodium benzoate (NaB) acts as a pH adjuster and enhances SAEW's anti -biofilm activity. The results showed that the SAEW combined with NaB (SAEW + NaB) is highly effective in controlling biofilm. The adhesive strength of biofilm was significantly reduced by SAEW, and NaB was found to have a synergy effect with SAEW. Biofilm treated by SAEW + NaB was entirely removed by 60 s of ultrasonic wave, whereas the untreated biofilm can only be removed to a lesser extent. Atomic force microscope (AFM) analysis revealed that SAEW and NaB reduced the height of S. mutans biofilm. The metabolites derived from biofilm positively changed during the periodic 1-min treat, the production of lactic acid was hindered by the treatment. Altogether, these findings suggested a novel therapeutic intervention against S. mutans biofilm by targeting the cariogenic action. Graphical abstract: Image 1 Highlights: SAEW + NaB strongly interferes with S. mutans adhesion to the surface of posterior notch tooth model. The acidity of S. mutans biofilm is alleviated by sodium benzoate. SAEW + NaB had an active role in metabolism during the formation of the S. mutans biofilm. This study provided one potential therapeutic targeting the cariogenic action of S. mutans.